Understanding phubbing behavior: A scoping review of qualitative and mixed-methods studies - Amélie Deschamps; Marie-Ève Fortier; Natalia Muñoz Gómez; Anne-Marie Auger; Caroline Fitzpatrick; Magaly Brodeur (Computers in Human Behavior Reports)
The use of smartphones has significantly increased in recent years, leading to the emergence of a new concept known as phubbing, which refers to being absorbed in one's smartphone while in the presence of others and neglecting interpersonal communication. Quantitative studies have highlighted the negative impacts of phubbing on, for example, relationship quality and satisfaction, as well as its predisposing factors. However, there is limited information on the experiences of those who engage in phubbing (phubbers) and those who are affected by it (phubbees). This scoping review aims to provide a comprehensive overview of the current understanding of phubbing derived from qualitative and mixed-methods studies. It follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for scoping reviews. Seven databases were searched for relevant studies, from which 251 articles were found. The title and abstract screening led to the full-text review of thirty-one articles, of which thirteen were retained and assessed for quality. Data extraction and narrative synthesis were then performed on the thirteen articles included in this study. Among these, seven were qualitative and six employed mixed methods. The results were divided into seven categories: (1) study characteristics, (2) definitions, (3) negative consequences, (4) positive factors, (5) social norms and contextual factors, (6) motives, and (7) strategies. The findings of this review highlight the need for further research to clarify phubbing terminology, explore its social norms across cultures, understand its impacts, identify mitigation strategies, and investigate the factors associated with phubbing in children and adolescents.